Active Aging In Long-Term Care Facilities In Korea : Beyond The Lexical Meaning. Issue 2 (17th February 2022) - Kim, Hyun-Jeong; Shin, Yumi; Ha, Jung-Hwa; Kim-Knauss, Yaeji
ABSTRACT: The discourse of active aging, as introduced by the WHO, aims at optimizing older adults' opportunities for health, participation, and security that could eventually enhance their social integration and quality of life. Considering that even those with frailty could strive for active aging in the given circumstances, we examined the meaning of active aging in long-term care settings and care strategies to promote it based on the WHO's framework. We conducted interviews with a total of 35 participants. The interpretative analyses revealed that the activities taken place in LTCFs have various scopes depending on older adults' physical and cognitive functional ability, and it captures the forms of activities that go beyond its lexical meaning. By defining being "active, " the present findings could contribute to an understanding of how the three elements of active aging can be carried out in LTCFs.